Analysis and design procedure of a mm-Wave Class-E power amplifier. (May 2021) - Ghasemizadeh Tamar, Habib; Nabavi, Abdolreza; Haghighat, Mohsen
Abstract: This paper presents a Class-E Power Amplifier (PA) design procedure for operation at mm-Wave frequencies, which accounts for the loss of passive components, ON-resistance ( R on ) of the transistor, and its breakdown voltage ( V Br ). The quality factor of inductors is modeled with equivalent resistors and integrated into time-domain equations for the first time. The proposed procedure is examined for the design of a 24 ​GHz Class-E PA in 130 ​nm CMOS technology and compared with former best-known design recipes in the same technology node. Besides, a simplified design technique is introduced based on R on -C out ( C out is the transistor output capacitance) curves of the transistor versus its width, obtained by Harmonic Balance (HB) simulation. By the proposed method, the Figure of Merit (FoM) of the designed PA, including a combination of the output power, efficiency, and maximum drain voltage, is improved significantly (52%) compared to the other procedure outcomes in the literature.